ISOLATION AND IDENTIFICATION OF STAPHYLOCOCCUS AUREUS FROM WOUNDS OF DAIRY CATTLE IN VITRO - Naimah Putri; Eka Legya; Mochammad Charis Hidayahtullah (Politek ATK Yogyakarta Press, 2022)
The skin is the largest organ of the body that can be infection. One of the causes of infections is microorganisms. The presence of Staphylococcus aureus on the skin of dairy cattle can affect the quality of leather. This research was conducted to isolate and identify S. aureus from the skin of injured dairy cattle. The sample was taken from a dairy farm in Surabaya. Isolation of S. aureus was carried out using NA and MSA selective media, while characterization was carried out using gram staining, catalase test, and coagulase test. The research results showed that samples isolated from wounds on the skin of dairy contained S. aureus. Gram staining test showed gram positive bacteria with coccus morphology and clustered arrangement. The catalase test was positive with the formation of H2O and O2. Catalase test was indicated by the formation of coagulation or clots in the blood plasma. These results indicated that the skin with contains S. aureus bacteria which can cause infection so that it can affect the quality of the skin to be tanned.